2019
DOI: 10.3171/2017.12.jns172386
|View full text |Cite
|
Sign up to set email alerts
|

Elevated markers of brain injury as a result of clinically asymptomatic high-acceleration head impacts in high-school football athletes

Abstract: OBJECTIVE This prospective observational cohort study of high-school football athletes was performed to determine if high-acceleration head impacts (HHIs) that do not result in clinically diagnosed concussion still lead to increases in serum levels of biomarkers indicating traumatic brain injury (TBI) in asymptomatic athletes and to determine the longitudinal profile of these biomarkers over the course of the football season. METHODS Sixteen varsity high-school football athletes underwent baseline neurocogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Clinically asymptomatic HHIs have already been associated with increases in serum tau and UCH-L1, both biomarkers of TBI. 13 Coupled with the QP data, an otherwise asymptomatic HHI potentially meets the criteria proposed for concussion by the CISG based on an objective biomechanical, physiological, and biomarker evaluation. Previous literature has suggested that there is a wide spectrum of mTBIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinically asymptomatic HHIs have already been associated with increases in serum tau and UCH-L1, both biomarkers of TBI. 13 Coupled with the QP data, an otherwise asymptomatic HHI potentially meets the criteria proposed for concussion by the CISG based on an objective biomechanical, physiological, and biomarker evaluation. Previous literature has suggested that there is a wide spectrum of mTBIs.…”
Section: Discussionmentioning
confidence: 99%
“…However, an HHI accounts for only 0.01% of all head impacts experienced by high school athletes. 13 Given this low incidence, an HHI appears to be an actionable entity. Previous studies have suggested that the frequency of high-speed collisions can be regulated out of football and, perhaps, other sports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarker discovery work in TBI has identified several promising blood protein biomarkers: glial fibrillary acidic protein (GFAP), ubiquitin C-terminal hydrolase-L1, neuron specific enolase and S100β (Wang et al, 2018). While these proteins may be useful biomarkers of acute and severe TBI, their use in reliably detecting milder forms of TBI remains to be fully investigated (Adrian et al, 2016;Joseph et al, 2018). At present, there are no blood biomarkers available for PTSD, and only broad inflammatory markers and cerebrospinal fluid (CSF) cortisone levels have been thoroughly examined (Schmidt et al, 2013;Michopoulos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%